2022
DOI: 10.1021/acs.iecr.2c02044
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Origins of High Selectivity of Metal Phosphides for Ethane Dehydrogenation

Abstract: Supercell density functional theory (DFT) calculations are used to create and exercise complete ethane dehydrogenation (EDH) reaction networks over Ni(111) and Ni 2 P(001). EDH intermediates are predicted to be more weakly bound to Ni 2 P than to Ni, with the differences being the greatest for deeply dehydrogenated intermediates. Both C−H and C−C bond cleavage activation energies are generally greater on Ni 2 P than Ni. The implications of these differences are explored through microkinetic models that incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…18) improves EDH selectivity and durability. A density functional theory (DFT) comparison of EDH performance on Ni(111) and Ni 2 P(001) 17,51 showed that P atoms selectively participate in adsorbate binding and C-H bond breaking, increasing activation barriers for steps leading to deep dehydrogenation and promoting ethylene desorption over ethylene overactivation. In addition, P incorporation weakens binding of small hydrocarbons, imparting coke resistance to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…18) improves EDH selectivity and durability. A density functional theory (DFT) comparison of EDH performance on Ni(111) and Ni 2 P(001) 17,51 showed that P atoms selectively participate in adsorbate binding and C-H bond breaking, increasing activation barriers for steps leading to deep dehydrogenation and promoting ethylene desorption over ethylene overactivation. In addition, P incorporation weakens binding of small hydrocarbons, imparting coke resistance to the surface.…”
Section: Introductionmentioning
confidence: 99%